KESTABILAN POPULASI MODEL LOTKA-VOLTERRA TIGA SPESIES DENGAN TITIK KESETIMBANGAN - Monica, Ritania; Deswita, Leli; Pane, Rolan (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article discusses the stability analysis of the population in Lotka-Volterra model of the three species. The analysis was conducted on the stability of the equilibrium point and the coordinate plane through linear analysis. Furthermore, some numerical examples show that the solutions obtained using the parameter values provide an overview of the development of the three species.